Successful management of left-sided bronchopleural fistula after left upper lobectomy without bronchial stump closure: a case report - Remi Yoneyama (The Egyptian Journal of Bronchology)
Abstract Background Bronchopleural fistula (BPF) is a rare but serious complication following lung surgery and is associated with significant morbidity and mortality, particularly in the first 2 weeks after surgery. BPFs are more common after right-sided resections, particularly pneumonectomy, than left-sided resections due to anatomical and physiological factors. Traditional management of postoperative pyothorax includes open-window thoracostomy (OWT) or thoracoplasty to control infection and promote pleural healing. In March 2023, the first Japanese guideline for the management of pyothorax was published, which recommended OWT or closure for BPF; this recommendation was based on level 2D evidence. In the case reported here, left-sided BPF was managed without direct bronchial stump closure or subsequent pyothorax cavity obliteration procedures, thereby emphasizing the importance of early diagnosis, effective drainage, and personalized management. Case presentation A 70-year-old man with clinical stage IB (T2aN0M0) squamous cell carcinoma of the left upper lobe had undergone thoracoscopic lobectomy. Fourteen days postoperatively, he presented with a fever of 37.4°C and an oxygen saturation of 94%. Laboratory tests revealed leukocytosis (13.9 × 103/μL) and elevated C-reactive protein level (22.6 mg/dL), indicating an inflammatory response. Computed tomography (CT) revealed left anterior pleural effusion, which was later diagnosed as empyema, while initial bronchoscopy revealed no obvious fistula. However, contrast injection after pigtail drainage confirmed a BPF. The empyema caused by the BPF was controlled with catheter drainage and antibiotics. Persistent air leak and difficulty in direct bronchial stump closure led to OWT on postoperative day 21. The patient recovered uneventfully within 35 days. After discharge, oral antibiotics were continued for 1 month. Follow-up imaging revealed no recurrence or residual infection, highlighting the effectiveness of early imaging-based diagnosis and management, which avoided surgical closure of BPF. Conclusions The present case demonstrates the effectiveness of innovative approaches that avoid bronchial stump closure for managing complex thoracic conditions, such as BPFs. The successful outcome suggests the potential for broader application of similar techniques, offering a viable alternative to more invasive procedures.